Autonomous Person-following Telepresence Robot Using Monocular Camera And Deep Learning Yolo - Ahmad Amin Firdaus Sakri; Noor Hanis Izzuddin Mat Lazim; Suffian At-Tsauri Mauzi; Mus’ab Sahrim; Liyana Ramli; Aminurrashid Noordin (ARQII Publication, 2024)
Indexed by Scopus